The Extension of the German CERAD Neuropsychological Assessment Battery with Tests Assessing Subcortical, Executive and Frontal Functions Improves Accuracy in Dementia Diagnosis - Schmid, Nicole S. (S. Karger AG, 2014)
BACKGROUND/AIMS: Alzheimer's disease (AD) is the most common form of dementia. Neuropsychological assessment of individuals with AD primarily focuses on tests of cortical functioning. However, in clinical practice, the underlying pathologies of dementia are unknown, and a focus on cortical functioning may neglect other domains of cognition, including subcortical and executive functioning. The current study aimed to improve the diagnostic discrimination ability of the Consortium to Establish a Registry for Alzheimer's Disease – Neuropsychological Assessment Battery (CERAD-NAB) by adding three tests of executive functioning and mental speed (Trail Making Tests A and B, S-Words). METHODS: Logistic regression analyses of 594 normal controls (NC), 326 patients with mild AD and 224 patients with other types of dementia (OD) were carried out, and the area under the curve values were compared to those of CERAD-NAB alone. RESULTS: All comparisons except AD-OD (65.5%) showed excellent classification rates (NC-AD: 92.7%; NC-OD: 89.0%; NC-all patients: 91.0%) and a superior diagnostic accuracy of the extended version. CONCLUSION: Our findings suggest that these three tests provide a sensible addition to the CERAD-NAB and can improve neuropsychological diagnosis of dementia.